1987
DOI: 10.3109/10641968709161458
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Characterization of DA-1 and DA-2 Dopamine Receptor Agonists in Anesthetized Rats

Abstract: This report summarizes studies aimed to characterize pharmacologically, hemodynamically and biochemically DA-1 (fenoldopam) and DA-2 (quinpirole) dopamine receptor agonists in anesthetized rats. Fenoldopam (20 micrograms/kg/min i.v. over 15 min) and quinpirole (10 micrograms/kg/min i.v. over 15 min) share the common property of decreasing mean carotid artery blood pressure by lowering peripheral vascular resistance. Fenoldopam increased mesenteric and renal blood flows whereas quinpirole decreased the former b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
19
0

Year Published

1987
1987
2004
2004

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 3 publications
2
19
0
Order By: Relevance
“…Blockade of peripheral dopamine D 2 receptors by intravenous domperidone enhances the maximal pressor response to quinpirole, as previously reported in normotensive, conscious rats (Nagahama et al 1986a(Nagahama et al & 1987. This agrees with previous reports that the peripheral dopamine D 2 receptor-mediated depressor effect, which is manifested in anaesthetized rats (Nagahama et al 1986b;Cavero et al 1987;Lahlou 1998), is masked by the central pressor effect of quinpirole in conscious rats (Nagahama et al 1986a).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Blockade of peripheral dopamine D 2 receptors by intravenous domperidone enhances the maximal pressor response to quinpirole, as previously reported in normotensive, conscious rats (Nagahama et al 1986a(Nagahama et al & 1987. This agrees with previous reports that the peripheral dopamine D 2 receptor-mediated depressor effect, which is manifested in anaesthetized rats (Nagahama et al 1986b;Cavero et al 1987;Lahlou 1998), is masked by the central pressor effect of quinpirole in conscious rats (Nagahama et al 1986a).…”
Section: Discussionsupporting
confidence: 82%
“…The site of action of quinpirole in the brain has been suggested to be the nucleus tractus solitarius (Yang et al 1990). In anaesthetized rats, quinpirole decreased blood pressure, an effect that is mediated partly by peripheral (Nagahama et al 1986b;Sengupta & Lokhandwala 1985;Lefevre-Borg et al 1987;Cavero et al 1987;Lahlou 1998) and partly by spinal dopamine D 2 receptor stimulation (Lahlou 1998). In conscious rats, the central influence of quinpirole predominates and masks the peripheral depressor effect.…”
mentioning
confidence: 99%
“…However, no significant changes occurred in this study with seven volunteers. In the study of Jeffrey et al (1988) Cavero et al (1987) demonstrated a rise of PRA by direct DA1 stimulation. The extent of increase in PRA during fenoldopam infusion was influenced by the presence of lithium and suggests that lithium enhances the effects of DA1-dopamine stimulation.…”
Section: Discussionmentioning
confidence: 83%
“…to the mankind and those in which the fused benzene ring is substituted at various positions have been found to be more potent.1) The research on the chemistry of indoles has continued unabated due to their wide spread occurrence in nature and biological activities [2][3][4] and the compounds in which the bio-active indole nucleus is spiro fused with another heterocycle at the C-3 position shows immense pharmaceutical applications.5-7) Further, spiro-3-indole derivatives, incorporating five and six membered heterocycles have been extensively reviewed [8][9][10][11][12] but few reports are available regarding those incorporating a seven membered thiazepine moiety. Also, 3-aroyl-2H-indol-2-ones (4a, b) have been found as the essential synthetic building block [13][14][15] for the synthesis of a wide variety of 3-spiro indolines and condensed indole derivatives.…”
mentioning
confidence: 99%